(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The rise of the metaverse economy creates an urgent need for pedagogical models that develop immersive skills, yet implementation in developing nations is hindered by a significant digital divide. This study aims to experimentally evaluate the effectiveness of the Metaverse-based. Based Learning compared to Blended Learning and Online Learning models in fostering the creative and digital business competencies required for this new paradigm. Employing a quasi-experimental design with 90 students, this research used pre-tests and post-tests, with data analyzed via ANCOVA and theoretically grounded in Cognitive Load Theory. The findings revealed a paradox: while the Blended Learning model produced quantitatively superior and more consistent competency scores, qualitative data showed Metaverse-Based Learning facilitated a fundamentally deeper, more authentic learning process characterized by active problem-solving and higher engagement. The study concludes that Metaverse-Based Learning’s quantitative inferiority is not a pedagogical failure but an artifact of excessive extraneous cognitive load from infrastructural barriers, proving that learning effectiveness is a multidimensional concept requiring a nuanced approach beyond standardized metrics.